Fatal Faultlines : Pakistan, Islam and the West - Irfan Husain (New York HarperCollins Publishers, 2012)
Fatal Fautlines has won the first prize at the Benjamin Franklin Awards in the US. Key Features Pakistani journalist Irfan Husain provides an analysis of common views held by Muslims about the United States The interviewees include political leaders, religious fundamentalists and ordinary citizens just struggling to survive The book would interest those who want to know more about the ordinary Pakistani and wish to hear his/her voice About the Book: Fatal Faultlines: Pakistan, Islam and the West Do people of different faiths, different histories and backgrounds share similar goals and objectives? How are citizens of Muslim countries different from Americans in their aspirations and perspectives? Does humanity, at its core, share common values-ones that can form the basis of peaceful co-existence for people from different parts of the world belonging to different religions? Do we really understand each other's perspectives? These questions have never been more important than they are now, as two societies stare at each other across an abyss that threatens to engulf us all. In Fatal Faultlines, veteran journalist Irfan Husain examines the motivations and attitudes of Muslims towards America. Drawing on personal experiences, interviews and decades of observations, he explains how different perceptions and misunderstandings have poisoned attitudes on both sides.
Include Bibliography and Index.
Irfan Husain Irfan Husain was born in Amritsar, India, in 1944 and migrated with his family to the newly created state of Pakistan three years later. Educated in Karachi, Paris and Ankara, he joined the civil service in 1967 after obtaining a master's degree in economics. He has pursued a parallel and covert career as a freelance journalist for most of his working life, writing under a succession of pseudonyms. As Mazdak, he became a popular columnist on the Internet edition of Dawn, a newspaper he has been writing for over the last two decades.
Keywords: Muslims--Attitudes -- Muslims--Political activity -- Public opinion -- United States -- Pakistan -- Western countries -- Diplomatic relations